Research in finance. - Chen, Andrew H. (Research in finance., 2005)
This volume contains contributions on important topics in current finance research. Topics include the impact of recent reform in corporate governance, the stock price reactions to the joint venture announcements, the temperature, and the financial signals, the pricing of SPARQs, the incentive effects in project finance with government financial guarantees, the option pricing models with price limits and market illiquidity, the benefits of financial competition and regulation, the banking theories on the required reserves and the impact of mid-loan bank lending, and the new tests PPP and the c.